Association of Radial Artery Access with Reduced Incidence of Acute Kidney Injury in Patient Undergoing Percutaneous Coronary Intervention - Muhammad Ikram Shinwari, Muhammad Idrees Khan, Tooba Hasan, Raza Muhammad Khan, Muhammad Ziyad, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Percutaneous Coronary Intervention (PCI) is a commonly performed procedure for treating coronary artery disease. However, one of the potential complications of this procedure is Acute Kidney Injury (AKI), which can result in significant morbidity and mortality for patients. Objectives of the study: The main objective of the study is to find the association of radial artery access with reduced incidence of acute kidney injury in patient undergoing percutaneous coronary intervention. Material and methods: This was a retrospective cohort study conducted at Medical Teaching Institute-Hayatabad Medical Complex, Peshawar between January 10, 2022 and June 13, 2022. The study was approved by the institutional review board. Data were collected from electronic medical records, including demographic information, medical history, procedural details, laboratory values, and outcomes. The primary outcome was the incidence of acute kidney injury (AKI), defined as an increase in serum creatinine of ≥0.3 mg/dL or ≥50% within 48 hours after the procedure. Results: Based on a study of 300 patients undergoing cardiac catheterization, there was a significant association between the use of radial artery access and reduced incidence of acute kidney injury (AKI). The odds ratio for radial artery access was 0.59 (95% CI 0.32-1.09), indicating a lower risk of AKI with this approach. This finding is consistent with the results presented in Table 3, which also showed a lower incidence of AKI in the radial artery access group. However, the p-value for radial artery access was 0.09, indicating that this association did not reach statistical significance. Conclusion: Based on the results of the study, it can be concluded that radial artery access may be associated with a lower incidence of acute kidney injury (AKI) and fewer bleeding complications compared to femoral artery access in patients undergoing cardiac procedures such as percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG).